Preanalytical processing of archaeological mammal enamel apatite carbonates for stable isotope investigations: A comparative analysis of the effect of acid treatment on samples from Northwest Australia. (29th July 2019) - Skippington, Jane; Veth, Peter; Manne, Tiina; Slack, Michael
Abstract: Stable isotopic analysis of palaeontological and archaeological biogenic apatite carbonates from herbivorous mammalian species represents an important tool for worldwide palaeoecological research. Tooth enamel carbonates are more resistant to taphonomic processes than bone or dentine carbonates but are not invulnerable to diagenesis. As such, they require careful preanalytical processing that considers depositional environment and age. An established part of this process includes a weak acid treatment to remove soluble exogenous carbonates; however, published treatment times for isotopic studies of archaeological tooth enamel are variable and range from 15 min to over 8 hr. This study tests three different pretreatment protocols on modern and Pleistocene age archaeological kangaroo teeth (dating from contemporary to 46, 000bp ) to assess the effect of acid treatment time on isotopic integrity. The results indicate that treatment time is a critical parameter for producing consistency across results and shorter pretreatments of 4 hr or less are preferable for removing diagenetic carbonates while minimising alteration of the biological signal.